Um estudo do termo “cerâmica icoaraciense" - MORAIS, Elizabeth Conde de (Universidade Federal do Pará, 2020)
This objective reflection define concepts related to the term Cerâmica Icoaraciense, from conception to show that the lexicon of a language is susceptible to change, with the innovation of words, just as the term is renewed to express the cultural practice carried out by the community. This analysis uses the readings from bibliographic studies dealing on Terminology, with reference Faulstich (1998), Krieger e Finatto (2004) and Lara (1999), for which matter the institution of the meaning of the new term; texts scientific whose midpoint surveys pottery created in Icoaraci. This approach, interdisciplinary, relies on the constitution of term texts in the fields of anthropology and the social sciences. To endorse the discursive constitution of the term with the identity relation adopted the analysis Maingueneau (2008), since the appropriation of this new form of expression is an appropriation to justify cultural identity with their locus of creation.